The Level of Taxpayer Compliance in Paying Land and Building Tax in Karumbu Village, Langgudu District, Bima Regency (Journal of Social And Education Research, 2023)
This study aims to analyze the level of compliance of Land and Building Tax (PBB) taxpayers in Karumbu Village, Langgudu District, Bima Regency. The research focuses on identifying factors influencing taxpayer compliance, including awareness, education, income levels, government service quality, and law enforcement. The study uses a descriptive quantitative method with secondary data from 2016 to 2019 obtained from the local tax office and village administration records. The results show that taxpayer compliance fluctuated from 2016 to 2018 but increased significantly in 2019, rising from 68% to 80%. This improvement is associated with enhanced taxpayer awareness, the effectiveness of tax officers’ performance, and the support of the village government through counseling and supervision. Education and economic stability were also found to be important determinants of compliance. However, some obstacles remain, such as low education levels and limited public understanding of tax benefits. The study concludes that sustainable tax compliance requires a comprehensive strategy involving community education, improved fiscal service quality, and strengthened transparency in tax fund management.